On the Stability and Chemical Bond of Noble Gas Halide Cations Ngx+ (Ng = He – Rn; X = F – I) - Pino-Rios, R (John Wiley and Sons Inc, 2021)
Despite the belief that noble gases (Ng) are completely inert and cannot form stable molecules, a variety of Ng compounds have been reported under laboratory conditions and others were recently detected in the interstellar media, raising interest in knowing and studying their bond nature and the physicochemical properties associated with their stability. In the present work, a systematic analysis of the thermodynamic stability of noble gas halide cations (NgX+) at the CCSD(T)/def2-QZVP level have been performed. In addition, chemical bond was characterized through Natural Bonding Theory (NBO), Quantum Theory of Atoms in Molecules (QTAIM) and Energy Decomposition Analysis (EDA) with relativistic corrections. All methods suggest that NgX+ compounds possess a strong covalent bond. However, results show that only compounds containing Ar–Rn atoms are thermodynamic stable with a highly energetic and endergonic dissociation process. For these reasons, it is possible to suggest that several compounds that have not yet been reported could be obtained at the laboratory level or observed in the interstellar medium. © 2020 Wiley Periodicals LLC.